2011
DOI: 10.1007/s13246-011-0088-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the effects of iodine contrast media on standardised uptake values of FDG PET/CT images: an anthropomorphic phantom study

Abstract: This study aimed to quantify the amount of change in Standardised Uptake Values (SUVs) of PET/CT images by simulating the set-up as closely as possible to the actual patient scanning. The experiments were conducted using an anthropomorphic phantom, which contained an amount of radioactivity in the form of Fluorodeoxyglucose (FDG) in a primary plastic test tube and one litre saline bags, including the insertion of bony structures and another two test tubes containing different concentrations of iodine contrast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Using this ROI size, we measured an overestimate of almost 9% with the nominal CT‐based attenuation correction for the phantom configuration in which all tubes contain iodine (“7 iodine inserts”). A similar SUV overestimate was observed in Razak et al 61 and Yau et al 63 Our investigation into the sensitivity of the improved stability on the selected measurement ROI radius R revealed that the behavior of mean SUV curves measured with smaller and larger ROIs persisted in both smaller and larger values of R (Fig. 6), attesting to the correctness of the ED‐based PET attenuation correction approach which offers the potential of reducing bias due to the presence of iodine.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Using this ROI size, we measured an overestimate of almost 9% with the nominal CT‐based attenuation correction for the phantom configuration in which all tubes contain iodine (“7 iodine inserts”). A similar SUV overestimate was observed in Razak et al 61 and Yau et al 63 Our investigation into the sensitivity of the improved stability on the selected measurement ROI radius R revealed that the behavior of mean SUV curves measured with smaller and larger ROIs persisted in both smaller and larger values of R (Fig. 6), attesting to the correctness of the ED‐based PET attenuation correction approach which offers the potential of reducing bias due to the presence of iodine.…”
Section: Discussionsupporting
confidence: 85%
“…Antoch et al 38 found contrast‐induced PET artifacts in 13% of patients in a study that included thirty oncology patients who underwent whole‐body PET/CT scans. Razak et al 61 quantified the effect of iodine contrast media on SUV of FDG PET/CT images in a semi‐anthropomorphic phantom and found mean overestimates of about 10%. Kinahan et al 2 performed simulations of an abdomen‐sized object to assess the effect of incorrect LAC mappings of iodinated contrast agents and the ability to correct these errors using spectral information from DECT acquisitions.…”
Section: Discussionmentioning
confidence: 99%
“…This study presents a novel design and 3D printing of an anthropomorphic, population-based, and customisable male and female TKR phantom which can be filled with any bone attenuation equivalent fluids and injected with any appropriate radiopharmaceutical to mimic human TKR PET/CT scans. A range of solutions can be diluted in water and injected into the TKR phantom to simulate either cortical or trabecular bone such as iodinated contrast media or dipotassium hydrogen phosphate (K 2 HPO 4 ) which has been used in previous studies to mimic a range of HU values [ 14 , 22 ]. In our experiment, iodinated contrast media was used as it was easy to source and it allowed the TKR phantoms to be used with adjustable HU values for testing any optimisation method applied to reduce the associated metal artefacts that arise in the PET/CT scans.…”
Section: Discussionmentioning
confidence: 99%
“…On anthropomorphic phantom with and without Iodine Contrast Media (ICM), the study conducted by Razac et al revealed a marginal absolute difference ΔSUV max and ΔSUV mean , of 0.2 and 0.4, respectively ( 18 ). This disparity was more pronounced in the most metabolically active simulated lesion (ΔSUV = 1.5 for a SUV max of 22).…”
Section: Physical Impact On Standardized Uptake Valuementioning
confidence: 99%